Bilateral vision loss in a patient with weight loss and neurologic symptoms - La Mancusa, Antonia; Rech, J.; Harrer, Thomas; Knorr, H.; Bergua, A. (Klinische Monatsblätter für Augenheilkunde, 2011)
EVALuna2:12701

Pattern electroretinograms during the cold pressor test in normals and glaucoma patients - La Mancusa, Antonia; Horn, Folkert; Kremers, Jan; Huchzermeyer, Cord; Rudolph, Michael; Jünemann, Anselm (Investigative Ophthalmology & Visual Science, 2014)
To examine the influence of the cold pressor test (CPT) on steady-state pattern electroretinograms (PERG) in healthy subjects and glaucoma patients.Steady-state PERGs to 7.8 Hz pattern reversal stimuli were recorded in 63 subjects. Fifteen healthy control subjects, 14 patients with ocular hypertension (OHT), and 34 patients with open-angle glaucoma (20 normotensive [NTG] and 14 high tension glaucoma [HTG]) were examined. Steady-state PERG amplitudes and latencies were analyzed at baseline, during cold stimulus using a modified CPT, and during the subsequent recovery phase. Blood pressure and heart rate were simultaneously recorded in 10 normals and 11 glaucoma patients.During the three test conditions (baseline, ice water, and warm water) glaucoma patients (NTG and HTG) showed significantly reduced PERG amplitudes in comparison with control subjects (P < 0.001) and with OHT patients (P < 0.004). Patients with OHT displayed lower PERG amplitudes than control subjects (nonsignificant, with consideration of Bonferroni). Only NTG patients showed a significant effect of the CPT on PERG amplitude (significant decrease during warm water P = 0.02). Latencies shortened significantly during warm-water period after cold stimulus in control subjects (P = 0.05) and in NTG patients (P = 0.02) with a nonsignificant trend of shortened latencies in the OHT (P = 0.06) and HTG groups (P = 0.3). Systolic and diastolic blood pressure increased during cold water (P < 0.001) and decreased during warming-up conditions (P < 0.001).This study shows that a CPT influences the PERG responses particularly in NTG. (ClinicalTrials.gov number, NCT00494923.).
EVALuna2:21162